Soy isoflavones recover pancreatic islet function and prevent metabolic dysfunction in male rats. Issue 3 (7th July 2021) - Ribeiro, Tatiane Aparecida; Pavanello, Audrei; Tófolo, Laize Peron; de Oliveira, Júlio Cezar; Moraes, Ana Maria Praxedes de; Franco, Claudinéia Conationi da Silva; Prates, Kelly Valério; Martins, Isabela Peixoto; Palma-Rigo, Kesia; Torrezan, Rosana; Yeo, Erica; Gomes, Rodrigo Mello; et al.
Abstract : We tested whether chronic supplementation with soy isoflavones could modulate insulin secretion levels and subsequent recovery of pancreatic islet function as well as prevent metabolic dysfunction induced by early overfeeding in adult male rats. Wistar rats raised in small litters (SL, three pups/dam) and normal litters (NL, nine pups/dam) were used as models of early overfeeding and normal feeding, respectively. At 30 to 90 days old, animals in the SL and NL groups received either soy isoflavones extract (ISO) or water (W) gavage serving as controls. At 90 days old, body weight, visceral fat deposits, glycemia, insulinemia were evaluated. Glucose-insulin homeostasis and pancreatic-islet insulinotropic response were also determined. The early life overnutrition induced by small litter displayed metabolic dysfunction, glucose, and insulin homeostasis disruption in adult rats. However, adult SL rats treated with soy isoflavones showed improvement in glucose tolerance, insulin sensitivity, insulinemia, fat tissue accretion, and body weight gain, compared with the SL-W group. Pancreatic-islet response to cholinergic, adrenergic, and glucose stimuli was improved in both isoflavone-treated groups. In addition, different isoflavone concentrations increased glucose-stimulated insulin secretion in islets of all groups with higher magnitude in both NL and SL isoflavone-treated groups. These results indicate that long-term treatment with soy isoflavones inhibits early overfeeding-induced metabolic dysfunction in adult rats and modulated the process of insulin secretion in pancreatic islets.